Comparison of Intra-Annual Growth Variation of Northern Temperate Forest Trees - Burtley, Cindy L. (My University, 2014)
Biotic and abiotic factors that influence tree growth vary spatially and temporally within forests. Here I compare seasonal changes in diametric growth (biweekly measurements between February and September, and monthly measurements between October and January) among 441 randomly selected individuals of 16 northern temperate forest tree species at the Wabikon Forest Dynamics Plot (FDP) in the Chequamegon- Nicolet National Forest near Crandon, WI, USA. The Wabikon FDP is a long-term research plot in the Forest Global Earth Observatory (ForestGEO) network coordinated by the Smithsonian Institution. Intra-annual diametric growth was measured with stainless steel dendrometer bands and digital calipers that are accurate up to ? 0.02 mm. Ambient temperatures (especially < 0?C) influenced intra-annual stem diameter fluctuations, with significant shrinkage occurring during winter for all species, particularly Tilia americana. During the growing season, tree diameter was the most consistent predictor of growth among all trees. Angiosperm (deciduous) trees grew more than gymnosperms during 2013, and canopy illumination positively affected growth of all trees, particularly angiosperms. Total basal area of neighboring trees within 10 m negatively affected growth of small diameter trees, but this competitive interaction was not significant for medium-large trees. Species richness within 10 m had a significant positive effect on tree growth for all species combined. These observations provide valuable insights into environmental and ecological triggers of diametric growth, differences in species sensitivity to these triggers, and potential limitations of forest productivity in response to climate change and other landscape disturbances.
University of Wisconsin-Green Bay. Dissertations. "A thesis submitted in partial fulfillment of the requirements for the Degree of Master of Science in Environmental Science and Policy." Includes bibliography. Illustrations. LC classification: SD396. Approved: Dr. Amy Wolf, major professor and Dr. Gregory J. Davis, Director of Graduate Studies; committee members: Dr. Robert Howe, Mr. Gary Fewless.
Keywords: Trees--Wisconsin--Chequamegon National Forest--Growth--Forecasting.; Trees--Growth--Environmental aspects--Wisconsin--Chequamegon National Forest.; Tree diameters; Measurements; Wabikon Forest Dynamics Plot.; Trees--Wisconsin--Chequamegon National Forest--Growth.